The Evolution of Islamic Civil Law in Indonesia: Developments, Contemporary Challenges, and Future Directions - Dewi Fransiska Mamonto; Selfrinda Rezkita Mahmud; Risnawati Utina; Geya Sukmawati; Fahira Nadra Male (Islamic Research Publiser, 2024)
This article explores the development of Islamic civil law in Indonesia, focusing on the areas of marriage and inheritance. It traces how Islamic legal norms have evolved during the reform era, examining both their practical implementation and the intellectual discussions that accompany them. The development of Islamic civil law reflects Indonesia’s ongoing efforts to harmonize Islamic legal values with the country’s plural legal system, which accommodates religious, customary, and state laws. The study uses a normative juridical method with a historical and conceptual approach. It analyzes primary and secondary legal materials, including statutory regulations, judicial decisions, and academic literature, to understand how Islamic civil law has been interpreted and adapted in the Indonesian context. Key issues discussed include the legal status of children born out of wedlock, marriage registration, polygamy, mandatory wills (wasiat wajibah), substitute heirs (ahli waris pengganti), and other aspects related to marriage and inheritance. The findings show that the development of Islamic civil law in Indonesia represents both continuity and change. While it maintains the essence of Islamic legal principles, it also responds to contemporary social realities, gender equality concerns, and the need for legal certainty. This adaptation demonstrates the dynamic nature of Islamic law and its capacity to evolve in line with societal transformation. Academically, this research contributes to the discourse on Islamic legal reform and legal pluralism by providing a comprehensive understanding of how Islamic civil law functions within Indonesia’s modern legal framework.